Analysis of Mental Health Policy in the Education Sector: Reviewing Disciplinary Methods in Schools - Lumastari Ajeng Wijayanti; Jihan Jihan; Satryo Sasono; Musbatul Mardiyah; Najamuddin Petta Solong (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Mental health and education are essential for a country to develop appropriately. This is because society in the future will depend on the quality of education today. Even the quality of education participants depends on the quality of existing mental health. This research was carried out to look at the mental health policies in Indonesia’s education sector. The method used in this study is a qualitative approach. The data used in this research comes from various research results and previous studies still related to mental health in the education sector. The results of this study then found that mental health in Indonesia, especially in the education sector, can be realized and improved by implementing the UKS program. By implementing well-planned and evaluated programs, the physical and mental health of the community in the education sector can be carried out effectively and efficiently. The optimal implementation of the UKS program includes health education and changes and habits in clean and healthy living behavior, both physically and psychologically healthy. It is crucial to support this with three strengths, namely institutions, cognitive frameworks, and social networks, so they can form healthy mental habits based on the school